DESIGN OF INTERACTIVE MULTIMEDIA AS LEARNING MEDIA ABOUT POLLUTION FOR ELEMENTARY SCHOOL STUDENTS - Yoga, Vincentius; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Pollution is a serious problem faced by humans because it can harm ecosystems and human health. Pollution generally occurs due to human activities that can damage ecosystems, such as industry, transportation, and waste. Understanding about pollution needs to be introduced early, especially to elementary school students, so that they have environmental awareness from an early age. Learning about pollution requires media that is interesting and easily understood by children. One effective solution is the use of interactive multimedia in the learning process. Interactive multimedia combines elements of text, images, audio, video and animation packaged in one interesting media. This media not only conveys information, but also allows students to interact directly with learning materials. Through the design of interactive multimedia about pollution, the learning process becomes more fun, communicative, and educational. With the existence of interactive multimedia as a learning media about pollution, it is hoped that students can understand and implement material about pollution into their daily lives and participate in preventing pollution.